HUBUNGAN TINGKAT PENDIDIKAN FORMAL DENGAN PERHATIAN ORANG TUA SISWA SDN 3 KEMUNING BANJARBAR - Inuriya Verawati (Pahlawan, 2020)
The formal education level has a certain period of time and runs from elementary to university with coverage besides the general academic field of study, as well as various special programs and institutions for field technical training. The aim of this research is to find out the relationship between the level of formal education and the attention of parents of students of the 3 elementary schools in Kemuning Banjarbaru. The research method used in this research is quantitative descriptive method. This research uses purposive sampling technique sampling is intentional sampling and randomized back. Samples were taken from 15 VA class students and 15 class VB School students at the State Elementary School 3 of Kemuning Banjarbaru. So the total number of samples was 30 students in grade V of the Public Elementary School 3 Kemuning Banjarbaru. This study uses 2 data mining tools, namely Questionnaire and Interview which are analyzed using data analysis techniques of this study using product moment analysis. Based on the results of the processing and analysis of research data, it can be concluded that there is a relationship between the level of formal education with parents' attention in Banjarbaru State Elementary School 3. This can be seen based on data analysis which shows that the results of r count = 8.512 is greater than r table with a significant level of 5% of 2.048 and r count = 8.512 can be proven that the alternative hypothesis (Ha) is related to the level of formal education with parents' attention State Elementary School 3 Kemuning Banjarbaru students at a significant level of 5% and declared accepted and the null hypothesis (H0) was rejected.